Transformasi Perpustakaan UNP Dalam Mencapai Universitas Negeri Padang Menuju World Class University - Sajida, Hana Putri; Nelisa, Malta (Scinary, 2025)
This study aims to describe the physical and non-physical transformation carried out by the State University of Padang (UNP) Library in order to support the university towards world-class university status. The background of this study is that there are some gaps in the contribution of the UNP Library to the vision. The research method used is a qualitative case study with data collection techniques through observation, interviews, and documentation. The results showed that the UNP Library has carried out various physical and non-physical transformations to improve the quality of services to its users, which significantly contributes to the achievement of State University of Padang's vision of becoming a world-class university. However, there are still some aspects that need to be developed further so that this library can fully meet the indicators as a world-class library.